De-Lovely [videorecording (DVD)] - Winkler, Irwin; Kline, Kevin; Judd, Ashley (MGM Home Entertainment, 2004)
An original musical portrait of American composer Cole Porter, filled with his unforgettable songs. Porter looks back on his life as if it were one of his spectacular stage shows, with the people and events of his life becoming the actors and actions onstage. Through elaborate production numbers and popular hits, Porter's elegant, excessive past comes to light - including his deeply complicated relationship with his wife, Linda Lee Porter, who was his inspiration.